The importance of nodal plane orientation diversity for earthquake focal mechanism stress inversions - Jens-Erik Lund Snee (22681070) (2025)
The Supplementary Data includes tables of the individual lineament orientations, the synthetic focal mechanism datasets used for the stress inversions and the results for each inversion group.